2021
DOI: 10.3389/feart.2021.775497
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Application of Molecular Dynamics to the Study of Coalbed Methane Geology

Abstract: Over the last three decades, molecular dynamics (MD) has been extensively utilized in the field of coalbed methane geology. These uses include but are not limited to 1) adsorption of gaseous molecules onto coal, 2) diffusion of gaseous molecules into coal, 3) gas adsorption-induced coal matrix swelling and shrinkage, and 4) coal pyrolysis and combustion. With the development of computation power, we are entering a period where MD can be widely used for the above higher level applications. Here, the application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 131 publications
(169 reference statements)
0
4
0
Order By: Relevance
“…Coal macromolecule was consisted of aromatic clusters, aliphatic chains, oxygen functional groups, and heteroatom groups (Given et al, 1986; Liu et al, 2019). After entering the 21st century, the research of coal molecular geochemistry has achieved fruitful results combined with the further development of computer-aided molecular design especially the development and progress of 13 C nuclear magnetic resonance (NMR), Fourier transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy and high-resolution transmission electron microscopy, providing the basis for the simulation of gas behaviors and coal geology (Song et al, 2021). The coal macromolecular representation used here was created via elemental analysis, 13 C NMR, FTIR, and high-resolution transmission electron microscope from Song et al (2019), whose predicted 13 C NMR spectrum was in line with the experimental results.…”
Section: Models and Calculation Methodsmentioning
confidence: 99%
“…Coal macromolecule was consisted of aromatic clusters, aliphatic chains, oxygen functional groups, and heteroatom groups (Given et al, 1986; Liu et al, 2019). After entering the 21st century, the research of coal molecular geochemistry has achieved fruitful results combined with the further development of computer-aided molecular design especially the development and progress of 13 C nuclear magnetic resonance (NMR), Fourier transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy and high-resolution transmission electron microscopy, providing the basis for the simulation of gas behaviors and coal geology (Song et al, 2021). The coal macromolecular representation used here was created via elemental analysis, 13 C NMR, FTIR, and high-resolution transmission electron microscope from Song et al (2019), whose predicted 13 C NMR spectrum was in line with the experimental results.…”
Section: Models and Calculation Methodsmentioning
confidence: 99%
“…Molecular simulations are increasingly popular for exploration in recent years. 17 Based on Newtonian mechanics, MD can supplement the process, which is impossible to measure in experiments. Meng et al 18 found that the affinity between methane and coal molecules reduced in the presence of water molecules, thus leading to less aggregation around the coal molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular simulations are increasingly popular for exploration in recent years . Based on Newtonian mechanics, MD can supplement the process, which is impossible to measure in experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Lin et al [12] established a multiphysics coupled model of diffusion, stress, and seepage fields and introduced the dynamic diffusion coefficient to explore the seepage evolution during gas drainage. In addition, some scholars have studied the desorption and adsorption behavior of coal at the microscopic level [13,14] and the influence of polymer on coal desorption and adsorption [15]. For the borehole spacing, too small spacing will increase the amount of work in the drilling construction and rise the instability risk of drilling such as pierce or collapse holes resulting from the pressure relief damage of coal and rock, while too large spacing will leave blind area of drainage, which not only can hardly eliminate the outbursts but also aggravate the hidden dangers of gas accidents [16].…”
Section: Introductionmentioning
confidence: 99%